A Dual Role of Heme Oxygenase-1 in Tuberculosis - Yang, Sen; Ouyang, Jing; Lu, Yanqiu; Harypursat, Vijay; Chen, Yaokai (Frontiers in Immunology, 2022)
Iron metabolism is vital for the survival of both humans and microorganisms. Heme oxygenase-1 (HO-1) is an essential stress-response enzyme highly expressed in the lungs, and catabolizes heme into ferrous iron, carbon monoxide (CO), and biliverdin (BV)/bilirubin (BR), especially in pathological conditions which cause oxidative stress and inflammation. Ferrous iron (Fe2+) is an important raw material for the synthesis of hemoglobin in red blood cells, and patients with iron deficiency are often associated with decreased cellular immunity. CO and BR can inhibit oxidative stress and inflammation. Thus, HO-1 is regarded as a cytoprotective molecule during the infection process. However, recent study has unveiled new information regarding HO-1. Being a highly infectious pathogenic bacterium, Mycobacterium tuberculosis (MTB) infection causes acute oxidative stress, and increases the expression of HO-1, which may in turn facilitate MTB survival and growth due to increased iron availability. Moreover, in severe cases of MTB infection, excessive reactive oxygen species (ROS) and free iron (Fe2+) due to high levels of HO-1 can lead to lipid peroxidation and ferroptosis, which may promote further MTB dissemination from cells undergoing ferroptosis. Therefore, it is important to understand and illustrate the dual role of HO-1 in tuberculosis. Herein, we critically review the interplay among HO-1, tuberculosis, and the host, thus paving the way for development of potential strategies for modulating HO-1 and iron metabolism.